Effects of hyaluronan and iodine on wound contraction and granulation tissue formation in rat skin wounds - Slavkovsky, R; Kohlerova, R; Jiroutova, A; Hajzlerova, M; Sobotka, L; Cermakova, E; Kanta, J (Clinical and experimental dermatology, 2010)
BACKGROUND: Hyaluronan (HA) plays an important role in the repair of damaged skin and has been used for the treatment of wounds. Iodine is a mild topical antiseptic. AIM: A mixture of high molecular weight HA with the iodine complex KI(3) (hyiodine) was reported to accelerate wound healing in patients with diabetes and patients after surgery. We investigated how this mixture affects wound contraction, granulation tissue (GT) and wound edges in excision skin wounds in rats. METHODS: Hyiodine was applied to full-thickness wounds made on the back of rats. The areas of the contracting wounds were calculated from digital photographs. The moving edges of the wound were studied by histological methods. The properties of GT were studied in wounds in which contraction was prevented by the insertion of plastic rings. The effects of hyiodine were compared with those of high molecular weight (1200 kDa) HA, low molecular weight (11 kDa) HA and KI(3) solution. RESULTS: Hyiodine accelerated wound contraction significantly in the first 5 days of healing. On day 3, hyiodine-treated wounds had reduced to 63% of the original area, whereas the wound area in saline-treated animals was 75% of the original size. The proliferating epidermis was thicker in hyiodine-treated animals on day 7. In the wounds with inserted rings, hyiodine caused little change in GT, but the weight of the crust/exudate formed on the top of the wound was increased by 351% compared with only minor changes caused by the hyiodine components alone. CONCLUSIONS: Hyiodine supports wound healing by stimulating wound contraction and epidermal proliferation and by keeping the wound moist through increased exudation.
Keywords: proteiny; Proteins; Granulation Tissue; Wound Healing; Gene Expression; Rats; Exudates and Transudates; kyseliny uronové; Contracture; granulační tkáň; hojení ran; kontraktura; preklinické hodnocení léčiv; Drug Evaluation, Preclinical; jod; Skin; exprese genu; mužské pohlaví; epidermis; Uronic Acids; Animals; Iodine; krysa rodu Rattus; kůže; Epidermis; exsudáty a transsudáty; kyselina hyaluronová; Hyaluronic Acid; Male; zvířata